ABOUT THE RELEVANCE OF TASKS TO LABORATORY WORKS FOR STUDENTS OF COMPUTER SCIENCES AND INFORMATION TECHNOLOGIES - Bazhan, Stanislav (Collection of scientific papers «ΛΌГOΣ», 2022)
The educational process is intellectual, creative activity in the sphere of education and science, which is carried out in the educational institution (scientific institution). The process takes place through the system of scientific-methodical and pedagogical measures and is directed on transfer, mastering, application and use of knowledge, skills and other competencies in the persons who study, and also on formation of harmonious developed personality [1].